Study on Sugarcane Production Efficiency Based on DEA-Malmquist Index: A Case Study of 8 Cities in Guangdong Province - Xiaohui Wang; Xin Zhang (Discrete Dynamics in Nature and Society)
This article takes the evaluation model of data envelopment analysis (DEA) and Malmquist index change and its decomposition method, from 2014 to 2018, of sugarcane production in 8 cities in Guangdong province as the research object and the selection of sugarcane production output and production factors as a model output variable and input variable, respectively, according to the eight cities of Guangdong province in 2014–2018 statistics and analyzes the sugarcane production efficiency of 8 cities in Guangdong province. The research results show that there are significant differences in the regional development level of sugarcane production comprehensive efficiency and the regional development imbalance of sugarcane industry in the eight cities of Guangdong province. The lower TPI of the eight cities is mainly due to the lower level of technological innovation. So as to put forward countermeasures which are university resource orientation for the sugarcane comprehensive efficiency in cities less than 1, transportation and telecommunication infrastructure, enhancement of the strength, the establishment of Guangdong province agricultural science and technology innovation alliance, and increase in sugarcane industry with modern manufacturing and the butt joint degree of the international marketing environment, the government actively build international BBS in sugarcane industries.